"Seroepidemiological Survey of Brucellosis Among Animal Farmers of Yazd Province" - MH Salari (Tehran University of Medical Sciences, 2002)
Brucellosis has remained a great problem of health in most of countries, which have failed in control of zoonosis infections. This disease is caused by species of Brucella and usually is transferred from animals to humans. The purpose of this study was to investigate the seroprevalence of brucellosis among animal farmers of Yazd province. In this descriptive study, 933 animal farmers were investigated by serological tests and blood culture method. Then the data were analyzed by SPPS statistical program. The results showed that the frequency distribution of seropositive cases by MAT and STAT were 35 (3.2%); 25 (2.7%) males and 10 (1.1%) females. The highest and lowest incidences of seropositive cases were among age group of 21-30 (1%) and more than 60 (0.3%) years old, respectively. Of the 35 seropositive cases, 2MET positive were 5 (0.5%), while all blood cultures were negative.